2004
DOI: 10.1111/j.1600-0463.2004.apm1120603.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Bartonella species in rodents, shrews and cats in Denmark: detection of two B. henselae variants, one in cats and the other in the long‐tailed field mouse

Abstract: Small mammals and stray cats were trapped in two areas of North Zealand, Denmark, and their blood cultured for hemotrophic bacteria. Bacterial isolates were recovered in pure culture and subjected to 16S rDNA gene sequencing. Bartonella species were isolated from five mammalian species: B. grahamii from Microtus agrestis (field vole) and Apodemus flavicollis (yellow-necked field mouse); B. taylorii from M. agrestis, A. flavicollis and A. sylvaticus (long-tailed field mouse); B. tribocorum from A. flavicollis; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
50
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(56 citation statements)
references
References 26 publications
5
50
0
1
Order By: Relevance
“…This prevalence was comparable to previous reports from other countries; ranging from 9% to 44% in Asia, 17% to 64% in Europe, 42% in North America, 44% in South Africa, and 29% in Australia. 5,8,9,11,[13][14][15]20,22,24,[38][39][40][41] Such high rates of Bartonella prevalence could be significant with respect to the risks of humans becoming infected with these agents. The commensal mammals harboring pathogenic microorganisms are often found in biotopes where they can come into close contact with humans who might therefore be at some risk of exposure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This prevalence was comparable to previous reports from other countries; ranging from 9% to 44% in Asia, 17% to 64% in Europe, 42% in North America, 44% in South Africa, and 29% in Australia. 5,8,9,11,[13][14][15]20,22,24,[38][39][40][41] Such high rates of Bartonella prevalence could be significant with respect to the risks of humans becoming infected with these agents. The commensal mammals harboring pathogenic microorganisms are often found in biotopes where they can come into close contact with humans who might therefore be at some risk of exposure.…”
Section: Discussionmentioning
confidence: 99%
“…20 Bartonella species associated with small mammals have been detected in Asia, Australia, North America, and Europe. 11,15,[20][21][22][23][24][25][26][27] Recent studies showed that bartonellae were widely distributed among rodents in South Africa 14 and among fleas in Democratic Republic of the Congo (DR Congo). 28 However, no study was conducted in small mammals of DR Congo or Tanzania.…”
Section: Introductionmentioning
confidence: 99%
“…California ground squirrels (Spermophilus beecheyi) are the main reservoir of B. washoensis, which has been identified in a human case of myocarditis [139] and in a case of endocarditis in a dog [50]. Finally, isolation of B. henselae type Houston I from three long-tailed field mice (Apodemus sylvaticus) was very recently reported [75] and raises an interesting question about the possibility of natural infection of wild rodents with B. henselae. Further studies will be required to determine if rodents could be another natural reservoir of this bacterium beside its feline reservoir.…”
Section: Rodent-borne Zoonotic Bartonellaementioning
confidence: 99%
“…In addition, because the Bartonella species are generally intra-erythrocytic agent, blood is used as a culture material (4,12,15,23). Liver tissue was used as blood supplement in this study due to the unavailability of mice blood samples.…”
Section: Resultsmentioning
confidence: 99%